FORMATION AND EVALUATION OF INNOVATIVE RESOURCE POTENTIAL OF ENTERPRISES - NYZHNYK, OLEG (Herald of Khmelnytskyi National University. Economic sciences, 2021)
For most domestic small and medium enterprises is characterized by the use of a system of indicators only of financial performance. Such systems are inconspicuous, because in modern conditions becoming increasingly important: assets of enterprises, market factors, innovation potential, etc. There is a need to form new criteria for assessing the level of innovation potential of enterprises, which would allow to cover all important areas of activity and the success of their interaction with the external environment. The developed systems of indicators are not sufficiently adapted to the Ukrainian realities, therefore they need some improvement and modification, which may be the subject of further research on the formation and increase of innovation potential and innovative development of small and medium enterprises. The article identifies the stages, content and principles of resource potential formation and approaches to assessing the innovation potential of small and medium enterprises. Evaluation indicators, which can be used to obtain comprehensive quantitative and qualitative information about the innovation potential and innovative development of the enterprise, forms a system of economic indicators. The formation and implementation of such a system contributes to sound planning, effective control and operational regulation of the level of innovative development of the enterprise. Based on the basic principles of forming a system of indicators for assessing the level of investment potential of enterprises, known systems of indicators and our own research, we have identified five groups of indicators for assessing the level of innovation potential of enterprises, namely: indicators of product innovation; indicators of resources for innovation (material, financial, labor, energy, information, intangible); indicators of innovation activity; indicators of the management system and indicators of the level of innovative development. Each of these groups characterizes a certain aspect of small and medium business.